Building the capacity of users and producers of evidence in health policy and systems research for better control of endemic diseases in Nigeria: a situational analysis - Obinna Onwujekwe (Globalization and Health, 2019)
Abstract Background There is a current need to build the capacity of Health Policy and Systems Research + Analysis (HPSR+A) in low and middle-income countries (LMICs) as this enhances the processes of decision-making at all levels of the health system. This paper provides information on the HPSR+A knowledge and practice among producers and users of evidence in priority setting for HPSR+A regarding control of endemic diseases in two states in Nigeria. It also highlights the HPSR+A capacity building needs and interventions that will lead to increased HPSR+A and use for actual policy and decision making by the government and other policy actors. Methods Data was collected from 96 purposively selected respondents who are either researchers/ academia (producers of evidence) and policy/decision-makers, programme/project managers (users of evidence) in Enugu and Anambra states, southeast Nigeria. A pre-tested questionnaire was the data collection tool. Analysis was by univariate and bivariate analyses. Results The knowledge on HPSR+A was moderate and many respondents understood the importance of evidence-based decision making. Majority of researcher stated their preferred channel of dissemination of research finding to be journal publication. The mean percentage of using HPSR evidence for programme design & implementation of endemic disease among users of evidence was poor (18.8%) in both states. There is a high level of awareness of the use of evidence to inform policy across the two states and some of the respondents have used some evidence in their work. Conclusion The high level of awareness of the use of HPSR+A evidence for decision making did not translate to the significant actual use of evidence for policy making. The major reasons bordered on lack of autonomy in decision making. Hence, the existing yawning gap in use of evidence has to be bridged for a strengthening of the health system with evidence.